PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN DAN PENGENDALIAN HIPERTENSI (PITIMAS: Journal of Community Engagement in Health, 2026)
Hypertension is one of the non-communicable diseases that has become a public health problem due to its continuously increasing prevalence and its risk of causing complications such as heart disease, stroke, and kidney failure. Based on the results of a community health assessment in RW 15, Pebatuan Village, Kulim District, Pekanbaru City, hypertension was identified as one of the priority health problems that is still influenced by the community’s low level of knowledge regarding risk factors, prevention, and management of the disease. Therefore, a community empowerment activity was carried out using a promotive and preventive approach to increase public knowledge and awareness in preventing and controlling hypertension. The community service activity was conducted from April to May 2025 using health education methods, hypertension exercise, and blood pressure screening for the community. All activities were carried out using an Interprofessional Education (IPE) approach involving students from various health professions to improve the effectiveness of public health services. The results of the activity showed that the community had a high level of enthusiasm during the education sessions. They gained an understanding of hypertension risk factors, the importance of regular blood pressure checks, the implementation of a low-salt diet, increased physical activity, cessation of smoking habits, and adherence to treatment for people with hypertension. This community empowerment activity is expected to improve healthy living behaviors and encourage the community to actively participate in sustainable efforts for the prevention and control of hypertension.
Keywords: Hypertension; Community Empowerment; Health Education; Prevention; Control